Gene flow in microbial communities could explain unexpected patterns of synonymous variation in the Escherichia coli core genome. (2nd January 2016) - Maddamsetti, Rohan
ABSTRACT: Researchers contest the importance of gene flow in bacterial core genomes, as traditionalists view microbes as predominantly clonal, asexually reproducing organisms. Contrary to the traditional perspective, Escherichia coli core genes vary greatly in their levels of synonymous genetic diversity. This observation indicates that the relative importance of evolutionary forces such as mutation, selection, and recombination varies from gene to gene. In this paper, I highlight why the synonymous diversity observation is broadly relevant to researchers interested in the evolutionary dynamics of microbial populations and communities. I explain how a model of evolution called the coalescent relates neutral diversity (i.e. mutations with negligible fitness effects) to mutation rates, evolutionary time, and a parameter called effective population size. I then describe the possible ways in which mutation, selection, and recombination can explain observed patterns of synonymous diversity in E. coli. Finally, I describe a model for E. coli genome evolution in which different loci are subject to varying levels of gene flow among co-occurring microbes and viruses in the environment. Researchers can falsify the gene flow hypothesis by sequencing genes and strains isolated from stable microbiomes or by carrying out evolution experiments that trace gene genealogies in real-time.